2004
DOI: 10.1679/aohc.67.253
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in capillaries in the ischemic brain in Wistar rats

Abstract: The microvasculature in the brain plays a vital role in the maintenance of brain perfusion, and fulfills the dynamic requirements of normal brain functions. It is well known that collateral circulation can be induced by ischemia in cerebral infarctions, but it is not known whether cerebral ischemia affects microvasculatures in the ischemic region. In the present study, we examined quantitatively serial changes in capillaries following bilateral common carotid artery ligation in Wistar rats. After the animals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
2
14
1
1
Order By: Relevance
“…While focusing on morphological alterations due to the ischemic stimulus, we observed–at least in part–thinned endothelia, which is in line with findings from Taguchi et al [40] and Morris et al [41]. These authors had demonstrated a decreased diameter of ischemia-affected capillaries and microvessels in diverse brain regions following global brain ischemia.…”
Section: Discussionsupporting
confidence: 91%
“…While focusing on morphological alterations due to the ischemic stimulus, we observed–at least in part–thinned endothelia, which is in line with findings from Taguchi et al [40] and Morris et al [41]. These authors had demonstrated a decreased diameter of ischemia-affected capillaries and microvessels in diverse brain regions following global brain ischemia.…”
Section: Discussionsupporting
confidence: 91%
“…When MRI was performed 6 weeks after MCA occlusion, the VSI data showed that the vessels in the recovery region were significantly larger in diameter compared with homologous tissue in the contralateral hemisphere, and this was confirmed by LSCM 3D quantitative analysis. (Taguchi et al, 2004) reported that capillary diameter at the ischemic boundary became greatly enlarged by 4 weeks after occlusion, which seems to indicate that the interface between blood and neural tissues becomes thin and wide, which would be beneficial for exchanging substances between circulating blood and the ischemic tissue. We found that MRI and LSCM measurements of both VSI and MSL showed a strong correlation between the recovery region and normal contralateral tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, cerebral ischemia [17,26,32] as well as cerebral hypoxia [13] was reported to trigger angiogenesis. In these previous papers, angiogenesis was assessed by counting capillaries only in fixed brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological changes in capillaries, as well as increases in capillary density, have been reported in some brain ischemia models [19,26]. These reports are based on histological examination of fixed brain tissue, where vessel diameter can readily change during perfusion–fixation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation